Is Investment-Uncertainty Relationship Monotonic? - Das, Amaresh (Indian Journal of Finance, 2010)
A considerable number of empirical studies exist which incorporate different measures of uncertainty in analyzing its impact on investment. Whereas Caballero (1991), Hartman (1972), Abel (1983), and others point to the positive impact of uncertainty on capital intensity of production under irreversibility of investment, McDonald and Siegel (1986), Dixit and Pindyck (1994) find that uncertainty is damaging to investment. Their argument is that in the long-run, the user-cost effect would dominate and that increased uncertainty in the long run would increase the expected capital stock under irreversibility and can increase it even more under reversibility. Actually, however, whether the increase in the expected long-run capital stock is larger under reversibility or under irreversibility depends on the choice of parameter values. Almost the entire investment literature assumes a linear relationship between uncertainty and investment but the uncertainty- investment may be non-linear. Sarkar (2000) and later Abel and Eberly (1999) provide an excellent interpretation of the non-linear relationship between investment and uncertainty. Sarkar (2000) points out that an increase in uncertainty increases the probability that the investment threshold will be crossed so that the probability of investment taking place within a specified time period increases. Sarkar's approach to investment (which is an option pricing approach) suggests that the investment- uncertainty relationship can be described by an inverted U- shaped curve. It is strange that the entire empirical literature has ignored this.